Description of Phytomonas oxycareni n. sp. from the salivary glands of Oxycarenus lavaterae. - Kelly, S; Seward, E; Votýpka, J; Kment, P; Lukes, J (Elsevier, 2016)
Phytomonas spp. (phytomonads) are a diverse and globally distributed group of unicellular eukaryotes that parasitize a wide range of plants and are transmitted by insect hosts. Here we report the discovery and characterisation of a new species of Phytomonas, named Phytomonas oxycareni n. sp., which was obtained from the salivary glands of the invasive species of true bug Oxycarenus lavaterae (Heteroptera). The new Phytomonas species exhibits a long slender promastigote morphology and can be found both within the lumen of the insect host's salivary glands as well as within the cells of the salivary gland itself. Sampling multiple individuals from the same population post-winter hibernation on two consecutive years revealed that infection was persistent over time. Finally, phylogenetic analyses of small subunit ribosomal RNA genes revealed that this species is sister to other species within the genus Phytomonas, providing new insight into the evolutionary history of the clade.